The Influence of Leadership and Motivation on Employee Performance: A Case Study at PT Lingkar Sakti Mas Gas Station Banjarmasin - Aksay Aksay; Rina Rina; Adiprimadana Sanjaya Fanlia (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
This study examines the influence of leadership and motivation on employee performance at PT. Lingkar Sakti Mas Gas Station in Banjarmasin. The research problem is the suboptimal employee performance caused by a lack of leadership attention and low work motivation. The purpose of this research is to analyze the effect of leadership and motivation on employee performance, both partially and simultaneously. The study uses a quantitative method with an associative approach, involving all 32 employees as respondents using a saturated sample technique. Data collection was carried out through questionnaires, and the data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, and F-tests. The findings reveal that leadership and motivation both have significant positive effects on employee performance, both partially and simultaneously, with a coefficient of determination (R²) of 63.3%. This indicates that leadership and motivation explain 63.3% of the variation in employee performance. The study concludes that improving leadership integrity and enhancing motivational factors such as compensation and recognition are essential to optimize employee performance in the public service sector, particularly at gas stations.